Knowledge and Attitude of Pregnant Women Attending Antenatal Clinic to Cervical Cancer Screening in Pregnancy in Ibadan, Nigeria (2022)
Intensive global efforts are currently on-going to ensure the elimination of cervical cancer by 2030. To achieve this, identification of populations and settings to optimize implementation is important. Pregnant women in antenatal setting provide one of such opportunities. This cross-sectional study conducted among pregnant women in a tertiary health facility evaluates the knowledge and attitude of cervical cancer screening in pregnancy. A total of 372 of the 380 (97.9%) women responded to the survey. The knowledge about cervical cancer among the respondents was 16.0%, 27.0% with good knowledge about cervical cancer screening and 21.0% had been previously screened for cervical cancer. If offered in the index pregnancy, about 74.2% were willing to undergo the screening. The age of respondents (p < 0.001) and the knowledge about cervical cancer screening (p = 0.034) were statistically significant factors associated with the respondents’ attitude to screening in pregnancy. Fear of the screening affecting their pregnancies was the reason in about half of the 26.8% of the respondents unwilling to undertake cervical cancer screening in pregnancy. The knowledge about risk factors for cervical cancer among our participants was poor. However, the attitude of participants towards cervical cancer screening in pregnancy was good. While policy makers might find this encouraging to incorporate routine cervical cancer screening into maternity services, there is urgent need for more awareness creation among our pregnant women, adequate counselling to correct misconceptions and education on the benefits of cervical cancer screening among our parturient.